2018
DOI: 10.1016/j.physbeh.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal oxytocin reduces weight gain in diet-induced obese prairie voles

Abstract: Oxytocin (OT) elicits weight loss in diet-induced obese (DIO) rodents, nonhuman primates and humans by reducing food intake and increasing energy expenditure. In addition to being important in the regulation of energy balance, OT is involved in social behaviors including parent-infant bonds, friendships, and pair bonds. However, the impact of social context on susceptibility to diet-induced obesity (DIO) and feeding behavior (including food sharing) has not been investigated in a rodent model that forms strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 90 publications
(108 reference statements)
0
15
0
Order By: Relevance
“…In addition, acute injections of i.n. OXT over a 7‐day period were able to reduce fasting levels of insulin and also appeared to reduce fasting levels of glucose (not significant) in a DIO prairie vole model . Finally, twice daily s.c. OXT administration over a 4‐week period (0.2 mg kg ‐1 for the initial 2 weeks; 0.4 mg kg ‐1 for the final 2 weeks) decreased fasting blood glucose in a more translational DIO rhesus monkey model .…”
Section: Effects Of Oxt Treatment On Weight Loss In Obese Animal Modelsmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, acute injections of i.n. OXT over a 7‐day period were able to reduce fasting levels of insulin and also appeared to reduce fasting levels of glucose (not significant) in a DIO prairie vole model . Finally, twice daily s.c. OXT administration over a 4‐week period (0.2 mg kg ‐1 for the initial 2 weeks; 0.4 mg kg ‐1 for the final 2 weeks) decreased fasting blood glucose in a more translational DIO rhesus monkey model .…”
Section: Effects Of Oxt Treatment On Weight Loss In Obese Animal Modelsmentioning
confidence: 93%
“…Recent studies have shown that central, systemic, or i.n. administration of OXT decreases food intake, weight gain and/or BW in DIO rodents, in genetically obese rodents, in ovariectomised rodents and in a dihydrotestosterone‐induced rat model of polycystic ovary syndrome, as well as in DIO non‐human primates . Below, we review the potential mechanisms that contribute to the effects of chronic OXT in rodent and non‐human primate models of obesity.…”
Section: Effects Of Oxt Treatment On Weight Loss In Obese Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been some important discoveries about novel oxytocin functions, particularly its effects on food intake and body weight regulation [15]. Interestingly, as mentioned above, oxytocin was shown to have more marked effects on appetite, body weight, and fat mass in obese animals and humans than in their non-obese counterparts [7,9,10,12,15,16,19]. However, in a cross-sectional study that evaluated the interactions among circulating oxytocin, the menopause, and obesity in pre-and postmenopausal women, it was reported that circulating oxytocin levels were significantly lower in postmenopausal women, especially in obese postmenopausal women, and that circulating oxytocin exhibits significant negative associations with the menopause and body weight [37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these studies suggested that the administration of oxytocin led to a reduction in fat mass by promoting lipolysis in adipose tissue and decreasing the formation of new adipocytes [7,[14][15][16]. Interestingly, these effects of oxytocin on food intake and fat mass were more noticeable in diet-induced and genetically obese rodents [7,17,18], diet-induced obese prairie voles [19], obese rhesus monkeys [9], and obese humans [20][21][22].…”
mentioning
confidence: 99%